DETERMINATION OF ENERGY CONTENT, PHYTOCHEMICAL CONSTITUENTS AND ANTIOXIDANT ACTIVITY OF POTENTIAL WILD EDIBLE LEGUME; CANAVALIA ROSEA (SW.) DC. FROM NORTHERN KERALA - V., ASWATHI; A. K., ABDUSSALAM (International Journal of Current Pharmaceutical Research, 2020)
Objective: Major objective of this study is to determine the calorific value and antioxidant activity of Canavaliarosea. Methods: Petroleum ether extract of the seeds were tested qualitatively for twelve components. Calorific value in kJ/100g seed flour was determined based on the results of the proximate analysis. Enzymatic and non-enzymatic antioxidants were analyzed by standard procedures using UV-Visible Spectrophotometer. Results: C. roseais a perennial creeper with roughly circular compound leaves. Flowers are brightly pink-purple, in racemes. It is having large fruits up to 8-12 cm, with brown dormant seeds inside. Seeds were collected from banks of ‘Kabani’ River (Panamaram) and from various tribal hamlets in Wayanad district, Kerela. Preliminary phytochemical screening reveals the presence of eight compounds such as, tannins,saponins, flavonoids, cardiac glycosides, terpenoids, phenols, coumarins and phlobatannins. The analysis of nutritive value of seed has a higher value of crude protein (48.71 %) and crude carbohydrate (34.07). The calorific value of seed material was 1529.9kJ/100g seed flour. Enzymatic antioxidants superoxide dismutase (38.134 u/mg fw) and catalase (19.051 u/mg dw) then non-enzymatic antioxidants poly phenols (12.81 u/mg dw) and ascorbic acid (10.301 u/mg fw) were tested. All those tests show significant levels of antioxidants in the sample. Conclusion: Hence, the present study providing details about the place of collection, ethnobotanical information, energy content and antioxidant activity of Canavaliarosea.